The mediating role of Artificial Intelligence readiness on accounting students' learning performance: an exploration of communicativeness, interactivity, mobility and autonomy moderated by technology readiness - Han, Mengrong; Abdul Razak, Hasri Mustafa; Kharuddin, Saira (Elite Scientific Forum, 2024)
Focusing on the transformative impact of Artificial Intelligence (AI) and technology in accounting education, this study examines how AI readiness, as a mediating variable, and technology readiness, as a moderating variable, affect the learning performance of accounting students. The study used structural equation modelling (SEM) and multilevel analysis to construct a comprehensive theoretical framework with communicative, interactive, mobile and autonomous as the core constructs. Through a large-scale questionnaire survey (N=1000) of accounting students in several universities across China, this study revealed the mediating mechanism of AI readiness between educational technology characteristics and learning outcomes, as well as the moderating effect of technology readiness. The findings indicated that AI readiness significantly enhanced the positive effects of communicativeness, interactivity, mobility, and autonomy on learning performance, while technology readiness strengthened this mediating effect. This study not only enriches the theoretical knowledge in the field of accounting education, but also provides empirical evidence for colleges and universities to formulate AI-integrated education strategies and enhance students' digital literacy, which is of great significance in promoting the modernisation of accounting education and cultivating highquality accounting talents adapted to the smart era.